How blockchain promotes the sustainability of the cacao value chain / Cómo blockchain promueve la sostenibilidad de la cadena de valor del cacao - TRANSITIONS Program; Mockshell, Jonathan; Hidalgo Jaramillo, Francisco Javier; Steinke, Jonathan; Ivanova, Yovita; Gutierrez Ortiz, Daniel Eduardo (2024)
Blockchain technology provides a transparent and safe way to follow the journey of cacao beans from tree to bar. Tracking socially and environmentally responsible practices enables consumers to better understand the sustainability behind the process.